Increasing collaborative, pro-environmental activism: The roles of Motivational Interviewing, self-determined motivation, and self-efficacy. (August 2018) - Tagkaloglou, Sofia; Kasser, Tim
Abstract: We investigated factors that promote successfully pursuing collaborative activist pro-environmental goals. Undergraduate students were randomly assigned to undergo a single session of Motivational Interviewing or a directive, control intervention; immediately afterwards, they set two collaborative, activist pro-environmental goals and rated how self-determined and self-efficacious they felt about those goals. Approximately 7 weeks later, they reported their progress on the goals and re-rated how self-determined and self-efficacious they had felt about the goals while they were pursuing them. Self-determined motivation both prospectively and concurrently predicted goal progress. Motivational Interviewing helped the goal progress of those participants who, at pre-screening, reported engaging in many individual pro-environmental behaviors, but the more directive approach worked better for those participants who were less ready to change. These results suggest the importance of attending to motivational variables if one hopes to increase people's engagement in collaborative, activist pro-environmental behaviors. Highlights: Self-determined reasons for environmental goals promoted goal progress. Efficacy for environmental goals was unrelated to goal progress. Motivational Interviewing facilitated goal progress for highly-ready participants.